2015
DOI: 10.3892/etm.2015.2633
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-195 inhibits cell proliferation in bladder cancer via inhibition of cell division control protein 42 homolog/signal transducer and activator of transcription-3 signaling

Abstract: Abstract. microRNA (miR)-195 acts as a suppressor in multiple types of malignant tumors, including bladder cancer; however, the detailed function of miR-195 in bladder cancer remains largely unknown. The aim of the present study was to investigate the role of miR-195 in the regulation of bladder cancer cell proliferation and to determine whether cell division control protein 42 homolog (Cdc42)/signal transducer and activator of transcription-3 (STAT3) signaling acts as a downstream effector of miR-195 in bladd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…In the present study RT-qPCR analysis revealed that miR-195 was upregulated in RCC, whereas previous studies have shown that miR-195 is downregulated in the majority of types of cancer, including colorectal cancer (17), glioblastoma (18), bladder cancer (11,12), osteosarcoma (13), cervical cancer (14), gastric cancer (19), hepatocellular carcinoma (20), esophageal squamous cell carcinoma (10), breast cancer (21), non-small cell lung cancer (22) and prostate cancer (23). Therefore, the present study, to the best of our knowledge apoptotic rate of the ACHN cells with a characteristic low apoptotic rate.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…In the present study RT-qPCR analysis revealed that miR-195 was upregulated in RCC, whereas previous studies have shown that miR-195 is downregulated in the majority of types of cancer, including colorectal cancer (17), glioblastoma (18), bladder cancer (11,12), osteosarcoma (13), cervical cancer (14), gastric cancer (19), hepatocellular carcinoma (20), esophageal squamous cell carcinoma (10), breast cancer (21), non-small cell lung cancer (22) and prostate cancer (23). Therefore, the present study, to the best of our knowledge apoptotic rate of the ACHN cells with a characteristic low apoptotic rate.…”
Section: Discussioncontrasting
confidence: 75%
“…Therefore, in prostate cancer, miR-195 functions as a tumor suppressor partially by targeting BCOX1, Fra-1 and fibroblast growth factor 2 FGF2. In bladder cancer it has been demonstrated that miR-195 induces G1-phase arrest by targeting CDK4 (27), and inhibits bladder cancer cell proliferation, at least partially, through the inhibition of Cdc42/STAT3 signaling (12). miR-195 has been indicated to be associated with the glycometabolism in bladder cancer by suppressing glucose uptake through regulating the expression of GLUT3 (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study also showed that miRNA-93 is upregulated in BC and is associated with tumor stage and lymph node metastasis (Jiang et al, 2019). And studies have reported that miRNA-195 inhibits glucose uptake and proliferation of BC T24 cells by inhibiting GLUT3 expression (Fei et al, 2012), another study found that miRNA-195 inhibits BC cell proliferation by inhibiting Cdc42 / STAT3 signaling (Zhao et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies had demonstrated that some miRNAs were associated with tumorigenesis and development of various cancers [7,15]. Due to the differences of target genes, these miRNAs could act as oncogenes or tumor suppressors in a various types of human tumors [16].…”
Section: Discussionmentioning
confidence: 99%